Building up Trustworthiness in Qualitative Research to Improve the Quality of Education - Chummongkol, Pathompong; Sohsomboon, Pairoh; Yuenyong, Chokchai (Journal of Teacher Professional Learning Community (JTPLC) (Online), 2023)
Improving educational quality comes in part from educational research aimed at bringing about positive changes in educational administration. Thailand’s education system is deplorable. The majority of educational research is estimative research, which analyses numerical data and replicates the findings. As a result, qualitative research should be encouraged in studies that will serve as a guideline for increasing educational quality. Especially in the classroom. Researchers are especially concerned about the quality and trustworthiness of qualitative research, which is difficult to establish. As a result, qualitative research in education is scarce. So, in this post, we’ll discuss how to develop trust, which is the most crucial aspect of qualitative research to increase educational quality.